2006
DOI: 10.5194/angeo-24-725-2006
|View full text |Cite
|
Sign up to set email alerts
|

Relation between substorm characteristics and rapid temporal variations of the ground magnetic field

Abstract: Abstract. Auroral substorms are one of the major causes of large geomagnetically induced currents (GIC) in technological systems. This study deals with different phases of the auroral substorm concerning their severity from the GIC viewpoint. Our database consists of 833 substorms observed by the IMAGE magnetometer network in 1997 (around sunspot minimum) and 1999 (rising phase of the sunspot cycle), divided into two classes according to the D st index: non-storm (D st >-40 nT, 696 events) and storm-time ones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
116
2
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(137 citation statements)
references
References 26 publications
17
116
2
2
Order By: Relevance
“…Since the peak time for substorm onset to occur is at 23:00 MLT, the list by Frey et al (2004) Figure 1 shows the locations of SAMNET stations and substorm onsets included in this study. The substorm onsets are divided into those that occur during storm time conditions (D st <−40 nT, 83 subtorms) and non-storm time conditions (D st >−40 nT, 470 substorms), the cut off value of −40 nT is consistent with Viljanen et al (2006). The D st used is the daily mean value of D st for the day at which the substorm occurs taken from NOAA National Geophysical Data Center (NGDC, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the peak time for substorm onset to occur is at 23:00 MLT, the list by Frey et al (2004) Figure 1 shows the locations of SAMNET stations and substorm onsets included in this study. The substorm onsets are divided into those that occur during storm time conditions (D st <−40 nT, 83 subtorms) and non-storm time conditions (D st >−40 nT, 470 substorms), the cut off value of −40 nT is consistent with Viljanen et al (2006). The D st used is the daily mean value of D st for the day at which the substorm occurs taken from NOAA National Geophysical Data Center (NGDC, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the characteristics of ground magnetic field variations have tended to focus on higher latitude areas such as Fennoscandia, by looking at the time derivative of the horizontal ground magnetic field, dH /dt (Viljanen et al, 2001). In particular, a study by Viljanen et al (2006) on the relationship between substorms and H , using the International Monitor for Auroral Geomagnetic Effects (IMAGE) network concludes that the largest values of dH /dt appear soon after the expansion phase begins, although many events have larger values at later times. The size of max|dH /dt| increases with increasing latitude equatorward of the auroral oval, poleward of which it decreases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the directional distributions of dH /dt are much more scattered than those of the simultaneous baseline subtracted horizontal variation field vector H . Another study restricted to 833 selected substorms in 1997 and 1999, before a solar maximum, showed a similar behaviour (Viljanen et al, 2006). Turnbull et al (2009) performed a corresponding investigation for 553 substorms at mid latitudes in 2000-2003 just after a solar maximum.…”
Section: Introductionmentioning
confidence: 99%